2013
DOI: 10.3892/br.2013.146
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism rs11614913 in microRNA-196a2 is associated with an increased risk of colorectal cancer although not with tumor stage and grade

Abstract: Abstract. A C/T polymorphism (rs11614913) was identified in the microRNA (miRNA) 196a2 (miR-196a2) gene and was implicated in the susceptibility to cancer. Numerous studies have investigated its association with the risk of colorectal cancer (CRC). However, the results were inconsistent and inconclusive. The present meta-analysis was conducted based on the results of six published case-control studies comprising 1,754 cases and 2,430 controls (up to November, 2012). Odds ratios (ORs) and 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…They also reported a higher frequency of CC genotype (49%) in patients as compared to control (38%), while the genotype GG was more common in the control group (17%) as compared to patients (10%). The previous study has also shown that the two common variants: rs2910164 G/C, rs11614913 T/C were associated with the development of several diseases including type 2 diabetes mellitus (T2DM) [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also reported a higher frequency of CC genotype (49%) in patients as compared to control (38%), while the genotype GG was more common in the control group (17%) as compared to patients (10%). The previous study has also shown that the two common variants: rs2910164 G/C, rs11614913 T/C were associated with the development of several diseases including type 2 diabetes mellitus (T2DM) [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some meta-analysis studies evaluated the correlation between one miRNA and a single cancer susceptibility. Wang et al confirmed the association of the polymorphism, miR-196a2 rs11614913, with the risk of CRC, but not with tumor stage and grade ( 43 ). Some meta-analysis studies evaluated the correlation between one miRNA and a variety of cancer susceptibilities.…”
Section: Discussionmentioning
confidence: 99%
“…1). Reports have demonstrated that this particular polymorphism could alter mature miR196a2 expression and binding ability to target mRNAs [13,15]. This was not predicted by the bioinformatics tools based on searching for perfect Watson-Crick pairing between the miRNAs' seed sequence and the target mRNA sequence alone, or in combination with other rules, such as evolutionary conservation criteria to predict miRNA target sites [16].…”
Section: Introductionmentioning
confidence: 96%
“…Altered miR-196a2 expression levels have been reported in various types of cancer [10,11]. High expression levels of mature miR-196a2 were found to promote the migration and invasion of cancer cells in vitro [12,13].…”
Section: Introductionmentioning
confidence: 99%